Expediency of the study of the ESR1 [rs 2234693], CYP19A1 [rs2414096], and IL10 [rs1800896] single nucleotide polymorphisms as feasible markers of risk that malocclusion develops in persons born macrosomic - O. V. Garmash; Ye. M. Riabokon (Zaporozhye State Medical University, 2020)
The article deals with analyzing the influence of polymorphic variants of CYP19A1 [rs2414096, rs936306], ESR1 [rs2234693, rs9340799], RANKL [rs9594738, rs9594759], IL1 [rs1143627], IL6 [rs1800796] and IL10 [rs1800896] genes on malocclusion development in individuals born macrosomic. The purpose of this study is to investigate the influence of the polymorphic variants of the CYP19A1 [rs2414096, rs936306], ESR1 [rs2234693, rs9340799], RANKL [rs9594738, rs9594759], IL1 [rs1143627], IL6 [rs1800796] and IL10 [rs1800896] genes on malocclusion development in individuals of the Kharkiv Region and adjacent area population born macrosomic. Material and methods. In total, one hundred and sixty-one individuals participated in this multi-stage study (144 macosomic-at-birth individuals and 17 normosomic-at-birth persons). The study participants were divided into groups according to the value of their Dental Aesthetic Index (DAI), which characterizes the severity of dental disorders and defines the need for orthodontic treatment. Results. Moderate malocclusion (DAI values in the 26-30 point range) in the surveyed persons were associated with the ESR1 gene variants ([rs 2234693], an over-dominant model of inheritance), CYP19A1 ([rs2414096], an additive, dominant, and multiplicative model of inheritance), and IL 10 ([rs1800896], dominant model of inheritance). The polymorphism of the IL10 [rs1800896] gene was significantly associated with the development of both the moderate and significant malocclusion (a dominant model of inheritance). Protection against significant malocclusion (DAI values of 31-35 points) was associated with the IL10 variant gene ([rs1800896], the dominant model of inheritance). In the presence of the heterozygous GA genotype, the risk of developing disorders decreased by 6.7 times. Analysis of ESR1 gene variants [rs 2234693], CYP19A1 [rs2414096], and IL10 [rs1800896], performed back in childhood, may be the basis for identifying at-risk individuals to developing dental disorders and for developing personalized preventive measures. Conclusions. In individuals born macrosomic, the dependence of the dentoalveolar system state on the variants of CYP19A1 genes: A> G [rs2414096], ESR1: -397 T> C [PvuII], and IL10: -1082 G> A [rs1800896] has been revealed.